Analysis of Potential Spatial Conflicts at Coastal and Marine Zones : Integration of the Spatial Planning of Land and Coastal Water - ., Mujio; Adrianto, Luky (Sodality: Jurnal Sosiologi Pedesaan, 2016)
ABSTRACTAnalysis of potential conflict mapping that will be studied and discussed is part of one of the analyzes performed in the study of Spatial Planning Model Coastal Area With Spatial Approach Connectivity.The purpose of this study is the mapping of potential conflicts between activities in the coastal zone Bontang City’s. Identification of potential conflicts is very necessary in preparing coastal spatial planning. Management and control of the conflict will facilitate allocation of space by considering the interests of various partiesKeyword: conflic, zoning, spatial planning, zone, coastalABSTRAKAnalisis potensi konflik yang akan dikaji dan dibahas ini merupakan bagian dari salah satu analisis yang dilakukan dalam penelitian mengenai Model Perencanaan Tata Ruang Kawasan Pesisir dengan pendekatan keterkaitan spasial (Spatial Connectivity). Tujuan Penelitian ini adalah memetakan potensi konflik antar kegiatan di kawasan pesisir Kota Bontang.Identifikasi potensi konflik sangat diperlukan dalam menyusun recana tata ruang pesisii. Pengelolaan dan pengendalian konflik akan memudahkan pengambilan keputusan dalam memutuskan alokasi ruang yang mempertimbangkan kepentingan antar pihak.Kata kunci: konflik, zonasi, tata ruang, kegiatan, Pesisir